EVALUASI PARADE OGOH-OGOH SEBAGAI PENDUKUNG PENGEMBANGAN PARIWISATA BUDAYA DI KOTA DENPASAR - Aristrawati, Ni Luh Putu (Jurnal Master Pariwisata (JUMPA); Volume 05, Nomor 01, July 2018DO - 10.24843/JUMPA.2018.v05.i01.p08, 2018)
This article discusses the evaluation of ogoh-ogoh (giant effigies) parade based on three aspects, such as the implementation of ogoh-ogoh parade, the contribution of ogoh-ogoh parade to the development of cultural tourism in Denpasar and to provide recommendations for strategy implementation of ogoh-ogoh parade. This article used culture tourism and evaluation theory. The data presented in this article was collected through observations and complemented by interviews and other published sources with qualitative approach. The collected data analyzed by CIPP (Context, Input, Process and Product) evaluation model, expert judgment and qualitative descriptive. The result shows that ogoh-ogoh parade meet the criteria as an event that contributes as an effort to assert Denpasar as a cultural city. Ogoh-ogoh parade also contributes and supports Denpasar in developing cultural tourism. The implementation strategy of ogoh-ogoh parade can be done through competition and increasing promotion strategy. From this article it can be concluded that as one of the cultural events in Denpasar city ogoh-ogoh parade can support the development of cultural tourism in the city of Denpasar, although in its implementation it requires sustain improvement.